Incidence of Respiratory Tract Infection in Children with Cyanotic and Acyanotic Congenital Heart Disease: A Comparative Study - Syafira Yasmine; I Ketut Alit Utamayasa; Bambang Herwanto (Faculty of Medicine Universitas Airlangga, 2022)
Highlights:1. The incidence of respiratory tract infection (RTI) showed no difference between patients with cyanotic and acyanotic congenital heart disease (CHD).2. RTI patients with acyanotic CHD experienced longer hospital lengths of stay. AbstractIntroduction: Respiratory tract infection (RTI) is the leading cause of children mortality rate in the world. Congenital heart disease (CHD) is a common congenital disease that plays a role in RTI incidents. However, between the 2 types of CHD, which type that is more potential to cause the RTI is not well identified. The aim of this study was to compare the incidence and hospitalization time of RTI between 2 types of CHD and describe the profile of the patients based on gender, age, nutrition, and immunization status.Methods: This retrospective study identified the medical records of children with RTI and all types of CHD aged 0-18 years old at Dr. Soetomo General Hospital Surabaya. The diagnosis of CHD was observed by echocardiography and RTI was observed by clinical symptoms.Results: Of 135 patients, the incidence of RTI showed no difference between a patient with cyanotic and acyanotic CHD. The majority of the patient was aged less than 3 years old (93.3%) and dominated by male patients (53.3%). The frequency of children with severe underweight and good nutritional status was equal. There were 85 patients who had incomplete immunization based on their age. The most common type of acyanotic CHD was an atrial septal defect (ASD). Cyanotic CHD was dominated by the tetralogy of Fallot (ToF). Pneumonia was the common type of RTI (108/135). RTI patients with acyanotic CHD had a longer time of hospitalization than cyanotic patients (11 days).Conclusion: This study found that RTI patients with acyanotic CHD experienced longer hospital lengths of stay.